2017
DOI: 10.1002/2016jd026272
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of riming on snowfall using ground‐based observations

Abstract: Ground‐based observations of ice particle size distribution and ensemble mean density are used to quantify the effect of riming on snowfall. The rime mass fraction is derived from these measurements by following the approach that is used in a single ice‐phase category microphysical scheme proposed for the use in numerical weather prediction models. One of the characteristics of the proposed scheme is that the prefactor of a power law relation that links mass and size of ice particles is determined by the rime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(137 citation statements)
references
References 56 publications
13
124
0
Order By: Relevance
“…There are several ways to do such a fit, given that we are interested in comparing ground‐based and radar observations, the fitting is done by giving more weight to particles that contribute the most to the radar observations, as shown in . The comparison of the computed rime mass fraction values to the ones reported by Moisseev et al () shows a rather good agreement. Figure presents the comparison between equivalent LWP (ELWP) computed from FR and LWP measured by the MWR, as well as the cumulative distribution of LWP.…”
Section: Methodssupporting
confidence: 79%
See 3 more Smart Citations
“…There are several ways to do such a fit, given that we are interested in comparing ground‐based and radar observations, the fitting is done by giving more weight to particles that contribute the most to the radar observations, as shown in . The comparison of the computed rime mass fraction values to the ones reported by Moisseev et al () shows a rather good agreement. Figure presents the comparison between equivalent LWP (ELWP) computed from FR and LWP measured by the MWR, as well as the cumulative distribution of LWP.…”
Section: Methodssupporting
confidence: 79%
“…Moisseev et al () have followed this approach and have derived the mass‐size relation for unrimed snowflakes using the ensemble mean snow density retrieved by Tiira et al (). Using data collected during BAECC and winter 2014/2015, they have found that the relation mur()D=0.0053D2.05 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Precipitation in midlatitudes originates mostly from mixed‐phase cloud systems and growth of ice particles by the collection of supercooled liquid drops. This process, known as riming, contributes significantly to surface precipitation, see e.g., Grazioli et al () or Moisseev et al () for some observational evidence based on state‐of‐the‐art measurement techniques. For example at the coastal areas of Japan, heavily rimed snow particles are in fact present in more than 70% of the snowfall events and contribute more than 50% to wintertime surface precipitation (Harimaya & Sato, ).…”
Section: Introductionmentioning
confidence: 99%